PENGOLAHAN BONGGOL JAGUNG SEBAGAI MEDIA TANAM JAMUR JANGGEL DI DESA KURIPAN UTARA KECAMATAN KURIPAN KABUPATEN LOMBOK BARAT - Muh. Dhuhal Islam Ziadi; Wida Farhiyati; Rizka Dwi Indah Savitri; Riski Amelia; Arniwati Arniwati; Sri Mulya Jatiswari; Marsinah Marsinah; Ahmad Baehaqi; Lalu Taufik Hidyatullah; Muhammad Kurniawan; Siti Atikah (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
Kuripan Utara is one of the villages in Kuripan sub-district, West Lombok regency, West Nusa Tenggara province, Indonesia. Leading potential in the Kuripan Utara Village is agriculture. The obstacle faced by the community is the lack of awareness about the management of agricultural waste products, one of which is corncobs waste. Alternative solutions can be done to hold socialization of making mushrooms from corncobs media. The method used is the preparation of socialization programs and training in making mushroom growing media from corncobs. The results of this community empowerment program are providing information, knowledge, and training to the Kuripan Utara community on how to treat agricultural waste such as corncobs. Like a mushroom growing media, Corncobs can be used as raw material to make innovative food products that can increase agricultural waste's use and economic value.